Analisis Kemampuan Membaca Al-Qur’an Mahasiswa Fakultas Hukum Universitas Lampung - Friyansyah; Eka Suci Indria Sari; Rohani; Ujang Efendi (An Naba, 2024)
The pandemic several months ago had an impact on PAI's lecture patterns, especially on increasing Al-Qur'an learning in public universities. Online lectures require lecturers and students to teach and learn from their respective homes. The aim of PAI learning in public universities is the development of students' Islamic personality, the development of Muslim personality traits that adhere to the teachings of their religion. The skill of reading the Al-Qur'an is the key to achieving PAI lectures, as an achievement that cannot be separated from achieving understanding in other material. However, there are factors inhibiting learning the Koran, including low motivation from students, lack of discipline, changing learning patterns from high school to college, online learning. The research objective to be achieved is as follows: "Analyzing the Al-Qur'an Reading Ability of Students at the Faculty of Law, University of Lampung". It is hoped that the results of this research can add and develop insight into the map of students' Al-Qur'an reading abilities in studying Islamic Religious Education courses. research on students' ability to read the Koran using a descriptive research design with a quantitative approach where data processing was carried out using statistical methods. Through this research design, information will be obtained regarding the percentage of Al-Qur'an reading ability of Unila Law Faculty Students, educational background when learning to read the Qur'an, the community they join which is related to the activity of reading the Qur'an, learning conditions Al-Qur'an which is liked by students. The population in this study were students from the Faculty of Law, University of Lampung with purposive sampling of students from the Faculty of Law Class of 2022. Measuring the ability to read the Al-Qur'an used a scale for measuring the ability to read the Al-Qur'an and measuring students' motivation and educational background. The instrument was developed using a Likert scale and tested for validity and reliability using Smart-PLS. Next, after the data was collected, data analysis was carried out using multiple regression analysis. This analysis is used to determine whether there is a relationship between variables supporting students' ability to read the Al-Qur'an. Keywords: Ability, Reading, Students, Al-Qur'an